2010
DOI: 10.1007/s11747-010-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability to support end-to-end value chains: the role of supply chain management

Abstract: Many firms are increasing their focus on sustainability. However, this focus has primarily emphasized environmentalism and ethics. Enterprise value chains must develop and support a broader sustainability perspective to ensure that its consumer, business, supply chain, community and environmental relationships and interactions remain viable. Using public documents and Internet sites of major global firms, this article suggests a framework to define the dimensions of sustainability and the categories of initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
226
2
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(241 citation statements)
references
References 61 publications
(63 reference statements)
3
226
2
10
Order By: Relevance
“…A broad body of literature evolved around different aspects of responsible corporate behavior focusing on various corporate functions and academic disciplines such as management, marketing or supply chain management (cf., Closs, Speier, and Meacham 2011;McWilliams and Siegel 2001;Seuring and Mueller 2008). The concept of corporate social responsibility (CSR) is characterized by a broad variety of definitions (McWilliams and Siegel 2001) within and across research disciplines and has morphed significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A broad body of literature evolved around different aspects of responsible corporate behavior focusing on various corporate functions and academic disciplines such as management, marketing or supply chain management (cf., Closs, Speier, and Meacham 2011;McWilliams and Siegel 2001;Seuring and Mueller 2008). The concept of corporate social responsibility (CSR) is characterized by a broad variety of definitions (McWilliams and Siegel 2001) within and across research disciplines and has morphed significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, we follow the concept of the triple bottom line (Elkington 1998), which highlights the need for managers and their firms to focus concurrently on the social, environmental, and economic impact of corporate activity (Henriques and Rich-ardson 2004;Van Tulder and Van der Zwart 2006). The triple bottom line appears in the research disciplines of marketing (e.g., Closs, Speier, and Meacham 2011;Hult 2011;Hunt 2011) and SCM (e.g., Carter and Easton 2011;Pagell and Wu 2009;Tate, Ellram, and Kirchoff 2010) as a widely used concept among managers and scholars. Thus, in this paper we use the term CSR synonymously for similar concepts such as sustainability (cf., Hult 2011) or corporate responsibility (cf., Campbell 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed that a highly behaviorally integrated TMT will tend to take more sustainability-oriented actions than less behaviorally integrated TMTs. In this line of research, [98] holds that a firm's top management plays an important role in that firm's engagement in sustainability. Also, [99] hold that both a firm's human capital and its business leaders are important to that firm's sustainability orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to adjust to this constantly changing corporate environment, firms develop dynamic capabilities that lead to long-or short-term sustainable competitive advantages [16][17][18][19][20][21][22]. A number of studies in the SC sustainability literature domain have been focused on static capabilities and dynamic capabilities [16,[21][22][23][24][25][26][27]. However, the only attempt to classify a broad range of these sustainable dynamic capabilities is made in the work by Srai et al [15] where a classification of sustainable dynamic capabilities is presented as five SC dynamic capability clusters:…”
Section: Literature Reviewmentioning
confidence: 99%